Dolphins, Love and Enchantment: Tracing the Use of Cetacean Products in Brazil - Siciliano, Salvatore; Viana, Maria C.; Emin-Lima, Renata; Bonvicino, Cibele R. (Frontiers in Marine Science, 2018)
The human population of the Brazilian Amazon possesses a rich body of beliefs and practices that relate to river dolphins, which are also known as botos (Inia and Sotalia species). There is a widespread belief in their magical powers in relation to love enchantments. One form that this takes is ‘dolphin love charms’ and these are widely in use in northern Brazil, and also in the largest southern cities. This paper considers the trade of cetacean products in the form of love charms in Brazil. Samples were obtained in the north (n=70), northeast (n=3) and southeast (n=59) regions from 34 shops or municipal markets. A total of 38 of the 131 collected samples were evaluated by complete cytochrome b sequencing, revealing the use of two species: the Guiana dolphin (Sotalia guianensis) (n=3) and the domestic pig (Sus scrofa) (n=10) and samples containing no animal material (n=10) were also detected. Pigs are used to fake love charm products in Rio de Janeiro. However, whereas in the southeast there is no actual use of dolphin tissues in love charms, there is a widespread use of dolphin tissue in northern Brazil, including, muscle, eyes, penis and vagina. The data confirm a regular trade of dolphin products in large cities in the north and northeast of Brazil and the need for more intense actions from governmental agencies in order to curb this illegal trade.